Rightful Bargaining: Rural Women Making Claims for Social Provisions in China’s Targeted Poverty Alleviation Program - Peng, Rui Jie (Sociological forum (Randolph, N.J.), 2021)
Previous studies of claims-making on authoritarian states have focused on how the aggrieved use episodic protests to challenge the state’s authority or adopt alternative group strategies to circumvent repression. Few studies have thus far applied these insights regarding groups’ innovative strategies and their interactions with the state apparatuses to explore individuals’ claims-making at the microlevel. Based on 15 months of ethnographic fieldwork in southwest China, this study analyzes how rural ethnic minority Qiang women actively engage various levels of government officials to demand enhanced social provisions. These women play off stereotypical gender assumptions about them to appear as nonthreatening subjects who accommodate state priorities for poverty alleviation and social stability. They also engage state officials and exploit (not always successfully) the government’s official rhetoric and internal divisions to secure much-needed social provisions. I call this type of gendered individual claims-making “rightful bargaining.” Yet, paradoxically, the study also reveals that, because the state’s legitimacy is founded precisely on economic growth and the appearance of popular consent, the incremental material gains these women achieve inadvertently reinforce the authoritarian regime’s overall legitimacy, domination, and control.